Innovation diffusion, technological convergence and economic growth - Rainer Andergassen; Franco Nardini; Massimo Ricottilli (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2013)
The paper investigates the mechanics through which novel technological principles are developed and diffused throughout an economy consisting of a technologically heterogeneous ensemble of firms. In the model entrepreneurs invest in the discovery and in the diffusion of a technological principle and their profit flow depends on how many firms adopt the innovation and on how long it takes other entrepreneurs to improve it. We show that technological convergence emerges from the competition among entrepreneurs for the profit flow and characterize the economy's growth rate.
Keywords: O31; O33; O41; E19; 330